2012
DOI: 10.1007/s11207-012-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

Observational Tracking of the 2D Structure of Coronal Mass Ejections Between the Sun and 1 AU

Abstract: The Solar Terrestrial Relations Observatory (STEREO) provides high cadence and high resolution images of the structure and morphology of coronal mass ejections (CMEs) in the inner heliosphere. CME directions and propagation speeds have often been estimated through the use of time-elongation maps obtained from the STEREO Heliospheric Imager (HI) data.Many of these CMEs have been identified by citizen scientists working within the SolarStormWatch project (www.solarstormwatch.com) as they work towards providing r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 67 publications
(135 reference statements)
0
28
0
Order By: Relevance
“…Based on the typical error for the distance, the widths have an uncertainty of ±1.2 R . A similar study was recently completed by Savani et al (2009Savani et al ( , 2012 for four CMEs observed by SECCHI. As can be seen in the bottom right panel of Figure 6, the three widths increase with distance, except that the ejecta and total ICME width become constant or start to decrease on May 25 at 00:09 UT.…”
Section: Width Of the First Cmementioning
confidence: 70%
“…Based on the typical error for the distance, the widths have an uncertainty of ±1.2 R . A similar study was recently completed by Savani et al (2009Savani et al ( , 2012 for four CMEs observed by SECCHI. As can be seen in the bottom right panel of Figure 6, the three widths increase with distance, except that the ejecta and total ICME width become constant or start to decrease on May 25 at 00:09 UT.…”
Section: Width Of the First Cmementioning
confidence: 70%
“…Since r is fixed for a given LAT-map, the equation provides, for each image, the HEEQ longitude corresponding to this height. Equation (10) of Rouillard et al (2009) can be used to convert each latitude/longitude (λ, l) pair into β, A and in Equation (1) of Savani et al (2012) to compute PA,…”
Section: Appendix Coordinatesmentioning
confidence: 99%
“…If deformation is important, the computed magnetic flux could be underestimated, questioning the decreasing magnetic flux calculated for MCs at different solar distances. To compare the circular cross-section approach with deformed cross-sections, we plotted the linear relationship of the radial width and distance to the Sun proposed by Savani et al (2012), W = 0.14R + 0.04 (continuous line in the upper panel of Fig. 9).…”
Section: Forbush Decreases and MC Propertiesmentioning
confidence: 99%